Multifaceted Effects of Migration for Sustainable Future - Pun, Lal Bahadur (Dhaulagiri Journal of Sociology and Anthropology, 2019)
Migration has become a global phenomenon because the modern means of transportation has reduced the time of travel. It has not only been soaring globally but also it has been becoming intense in Nepal as well. In the context of Nepal, migration from village towards frontier proximities, towns and city centers has been increasing on everyday basis, which is a stumbling block for sustainable future of both origin and recipient communities because it is associated with social, economic, environmental and institutional attributes of the origin and recipient communities. In this field, very few attempts have been made by academia, professional and concerned authorities focusing on the effects of migration for sustainable future. Considering this reality, I attempted to explore the twofold effects of migration in both origin and recipient communities pleading the stories of three research participants such as one non-migrant and two migrants. In this paper, I implanted ethnographic methods to inscribe the stories of research participants. For this, I employed conversational interview and observation techniques. In addition to this, I put my theoretical positionality on the side of the migration pessimistic school of thought putting the migration optimistic school of thought away to reveal the negative results of migration. Thus, the stories of both non-migrant and migrants have been implored in informal settings. From the sustainable point of view, the departure of people created social, economic, environmental and institutional threats in the origin as well as recipient communities.